Pengaruh current ratio, debt to equity, debt to asset, return on asset, return on equity, net profit margin dan price earning ratio terhadap harga saham - Hardiyanti, Fitri; Munari, Munari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The study aims to determine and analyze the effect of the variable current ratio, debt to equity, debt to assets, return on assets, return on equity, net profit margin, and price earning ratio on stock prices in the infrastructure company PT BEI. This type of research is a quantitative research using secondary data. The sample used in this study were 38 infrastructure companies on the Indonesia Stock Exchange during the 2018-2021 period that met the criteria in this study. Sampling in this study using purposive sampling technique. The data analysis technique in this study uses multiple linear regression analysis techniques (multiple linear regression). Based on the result of this study, it is known that the variable Current Ratio, Debt to assets, has an insignificant negative effect on stock prices. Variables Debt to Equity, Return on Assets, Return on Equity, Net Profit Margin, and Price Earning have no significant positive effect on stock prices. The result of the test show that the variables are Current Ratio (CR), Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Price Earning (P/E) have a significant effect on stock prices